Pragmatic Presupposition of Netizen Comments on Instagram Related to Teddy Minahasa Case - Muhammad Zakaria Pasaribu; Yusni Khairul Amri; Dian Marisha Putri (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
One form of information and communication media that is very popular at this time is Instagram. This media can be used as a place to share videos and photos with each other. Not only that, there are also various features for users to interact with each other. One of them is the comment feature, which is a place for Instagram users to express their opinions. Therefore, there are many forms of presupposition in Instagram comments, and they are very diverse. With the various forms of speech contained in Instagram, there are also forms of preponderance. George Yule also divides the types of presupposition into six namely existential (existenziell), factive (faktiv), non-active (nichtfaktiv), lexical (lexikalisch), structural (strukturell), and counterfactual (kontrafaktisch) presuppositions. This analysis aims to describe the presuppositions in the comments contained in Instragram comments about Teddty Minahasa. The source of the data in this analysis is comments from Instagram netizens regarding the case of Teddy Minahasa. The results of the analysis found pragmatic presuppositions based on the types of presuppositions namely; factive presuppositions and lexical presuppositions. In this analysis it was found that there were 3 factive presupposition data and 5 lexical presupposition data.